PEMETAAN POSDAYA DI KABUPATEN SEMARANG DENGAN SISTEM INFORMASI GEOGRAFIS BERBASIS SCALABLE VECTOR GRAPHICS (SVG) - Sekar Ratnaningtyas; Priyo Sidik Sasongko; Helmie Arif Wibawa (Jurnal Masyarakat Informatika, 2012)
Posdaya (Pos Pemberdayaan Keluarga) is a public institution that aims to empower families. The initiator of Posdaya is Damandiri Foundation which implemented through the activities of Kuliah Kerja Nyata (KKN) in various universities, one of them is UNDIP. Up till now, the result of KKN UNDIP Posdaya is only represented by written reports each semester so that the development Posdaya can’t be monitored accurately and openly. Utilization of information technology, Internet, and integration using geographic side could be a solution to ease data exchange. The geographical side was handled by SVG (Scalable Vector Graphics), an application of XML (eXtensible Markup Language) used to represent graphic information in a compact and portable form. Waterfall model was used to develop the software. This undergraduate thesis produced web-based GIS (Geographical Information System) that can display mapping of Posdaya in every village in the district of Semarang based on SVG. Through GIS, LPM can view and control the development of Posdaya overall, as well as promote the potential of the area to the public.